Pengaruh Kinerja Lingkungan Terhadap Sustainability Report Dengan Kinerja Keuangan Sebagai Variabel Mediasi - Siti Amalia; M. G. Kentris Indarti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Sustainability reports play an important role in disclosing information about a company's social and environmental activities in maintaining its sustainability. The aim of this research is to test and analyze the influence of environmental performance on sustainability reports with financial performance as an intervening variable. The population of this research is manufacturing companies listed on the Indonesian Stock Exchange in 2020-2022. By using purposive sampling, 34 companies were obtained that met the criteria, so the total data for this research was 83. The data analysis technique used was linear regression with path analysis. The research results show that environmental performance has no effect on financial performance, financial performance has no effect on the sustainability report, environmental performance has no effect on the sustainability report, and financial performance is unable to mediate the effect of environmental performance on the sustainability report. Keywords: environmental performance, sustainability report, financial performance